When being wasteful appears better than feeling wasteful - Ro'i Zultan; Maya Bar-Hillel; Nitsan Guy (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
'Waste not want not' expresses our culture's aversion to waste. 'I could have gotten the same thing for less' is a sentiment that can diminish pleasure in a transaction. We study people's willingness to 'pay' to avoid this spoiler. In one scenario, participants imagined they were looking for a rental apartment, and had bought a subscription to an apartment listing. If a cheaper subscription had been declined, respondents preferred not to discover post hoc that it would have sufficed. Specifically, they preferred ending their quest for the ideal apartment after seeing more, rather than fewer, apartments, so that the length of the search exceeds that available within the cheaper subscription. Other scenarios produced similar results. We conclude that people may sometimes prefer to be wasteful in order to avoid feeling wasteful.
Keywords: D03; M31; 330; waste aversion; mental accounting; violation of dominance; counterfactual; regret; Konsumentenverhalten; Emotion; Verhaltensökonomik; Wohnungswechsel; Informationskosten; Willingness to pay